Perfil químico e caracterização físico-química do óleo de sementes das cultivares de melão : Valenciano Amarelo e Pele de Sapo (Cururbitaceae) cultivado em Boa Vista - Silva, Flavio Paulino da (2017)
The Cucumis melo L. melon belongs to the family of cucurbitaceae is of African origin, introduced in Brazil by the Europeans in the middle of the 1960. In Brazil the major producers are concentrated in the northeast region, especially in Rio Grande Norte state. The consumption of the fruit in general is carried out in natura form or through industrial processes, after seeds are discarded to the environment. In order to make feasible the use of these agroindustrial residues, this work presents the chemical and physico-chemical study of the oil of the seeds of two cultivars of melon of Boa Vista in the state of Roraima. From the melons seeds were extracted oils whose yields were 28.47% and 26.41% respectively for Valenciano and Pele de Sapo. The physico-chemical characterization was applied to the oils of Valenciano and Pele de Sapo, respectively, 125.02 g I2/100 g and 120.96 g I2/100 g for the iodine value, 187.80 mg KOH/g and 185.65 mg KOH/g for saponification index, 0.73 and 0.75 for acid number, 893.33 g/mol and 902.33 g/mol for the average molecular weight, 3.85 and 3.64 for olefinic/aliphatic hydrogen ratio. The analysis in the Infrared region showed absorption in the range of 1.745 cm-1 characteristic of the stretching of the carbonyl group (C=O) of esters and carboxylic acids. The analysis of the composition of the major fatty acids by CG indicates the presence of Palmitic, Linoleic (ω-6) and Oleic (ω-9) Seeds of both melon cultivars. The physical-chemical parameters point to the quality of the oils of the melon seeds as being appropriate for human consumption. The behavior of the thermal degradation was determined by the thermogravimetric analysis of the oils of the melon seeds Valenciano Amarelo and Pele de Sapo that occurred between 341.08 to 522.03 and 334.83 to 524.29, respectively.